Modeling the egg and larval transport pathways of the Antarctic toothfish (Dissostichus mawsoni) in the East Antarctic region: New insights into successful transport connections - Mori, Mao; Mizobata, Kohei; 溝端, 浩平; ミゾバタ, コウヘイ; Ichii, Taro; Ziegler, Philippe; Okuda, Takehiro (Fisheries Oceanography, 2021)
The Antarctic toothfish (Dissostichus mawsoni) is an important fishery species widely distributed in the Southern Ocean, especially in areas covered by sea ice. Understanding fish distributions and life cycles, including the transport and survival of eggs and larvae, is essential for the assessment and sustainable management of the fishery. However, owing to difficulties with in situ winter observations, information on the early life stages of D. mawsoni is lacking. Here, we investigated the transport pathways of fish eggs and larvae through a particle tracking study, using satellite-derived ocean surface velocities in the East Antarctic region, which includes important D. mawsoni habitats and exploratory fisheries. Our results indicate that particles released from continental slopes are more likely to be successfully transported to suitable settlement grounds than those released from the BANZARE Bank (the southern region of the Kerguelen Plateau), which is situated further north and has been hypothesized to be a potential spawning ground for D. mawsoni. This study demonstrates successful source–settlement connections in relation to ocean recirculation and suggests important settlement regions for D. mawsoni larvae in the East Antarctic region. 20H04970 21H03587 journal article